The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1152/ajpheart.1996.271.3.h834
|View full text |Cite
|
Sign up to set email alerts
|

Acute transient coronary sinus hypertension impairs left ventricular function and induces myocardial edema

Abstract: This study was performed to evaluate the direct and indirect effects of acute coronary sinus hypertension (CSH) on systolic and diastolic left ventricular (LV) function. Coronary sinus pressure was elevated to 25 mmHg for 3 h in eight pentobarbital-anesthetized dogs and then relieved. LV contractility was assessed by preload recruitable stroke work (PRSW) and end-systolic elastance (Ees). Diastolic function was assessed by the time constant of isovolumic relaxation (tau) and the end-diastolic pressure volume r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 0 publications
3
41
2
Order By: Relevance
“…Similar results were reported in a study of pig and rat myocardium in which crystalloid-induced myocardial edema was associated with an increase in stiffness and a decrease in the filling volume of the left ventricle (2). Pratt et al (27) also found that interstitial myocardial edema induced by acute transient coronary sinus hypertension depresses contractility and increases diastolic stiffness of the left ventricle in dogs. Contrary to these findings, a recent study of rat intestinal edema showed decreased stiffness and residual stress, which result in intestinal transit delay (28).…”
Section: Changes In Stress and Strainmentioning
confidence: 94%
“…Similar results were reported in a study of pig and rat myocardium in which crystalloid-induced myocardial edema was associated with an increase in stiffness and a decrease in the filling volume of the left ventricle (2). Pratt et al (27) also found that interstitial myocardial edema induced by acute transient coronary sinus hypertension depresses contractility and increases diastolic stiffness of the left ventricle in dogs. Contrary to these findings, a recent study of rat intestinal edema showed decreased stiffness and residual stress, which result in intestinal transit delay (28).…”
Section: Changes In Stress and Strainmentioning
confidence: 94%
“…This impedes fluid removal from the cardiac interstitium via myocardial lymphatics, which results in fluid accumulation in the left ventricle and left ventricular dysfunction [74,80]. Moreover, the increased central venous pressure increases coronary sinus pressure and, thus, coronary microvascular pressure resulting in fluid filtration into the cardiac interstitium and additional fluid accumulation in the left ventricle [74,80,81]. Meanwhile, the sympathetic neural responsiveness is disrupted due to the effect of ischemia on neural cells, as well as due to the increased levels of exogenous epinephrine which downregulate the expression of a-and b-receptors leading to reduced inotropic and coronary vasoconstrictor responses.…”
Section: Pathophysiological Disturbances and Hemodynamics During Cardmentioning
confidence: 99%
“…However, experimental studies have demonstrated that LV myocardial interstitial edema induces both systolic and diastolic LV dysfunction, increased coronary vascular resistance, and arrhythmias due to a decreased refractory period [26][27][28]. As mentioned above, mechanical alterations provide an increased myocardial stiffness as a consequence of an excessive interstitial water distribution and an alteration by the interaction of collagen fibres, leading to an increase in the diffusion distance needed to supply oxygen to the myocytes [29].…”
Section: Diagnostic Usefulness Of O/imentioning
confidence: 99%